Analysis of Generation Z Communication Behavior in Fulfilling The Needs For Job Vacancy Information (Case Study on Instagram Media @lokerlampung_) - Lintina, Mey (Universitas Gajah Putih, 2025)
This study explores the communication behavior of Generation Z in fulfilling job vacancy information needs through the Instagram account @lokerlampung_. Using a qualitative case study approach and the Uses and Gratification Theory, the research examines how cognitive, affective, personal, social, and escapism needs are met through digital media. Findings show that Generation Z communicates actively and selectively, frequently interacting with job content, saving and sharing posts, and engaging directly with the account. Instagram is used not only for information but also for emotional support and identity expression. The study concludes that @lokerlampung_ plays a vital role in how Generation Z seeks and processes job-related information.